1997
DOI: 10.1046/j.1365-2141.1997.d01-2113.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of Fas ligand in large granular lymphocyte leukaemia

Abstract: Summary. The T-cell type of large granular lymphocyte (LGL) leukaemia is a lymphoproliferative disorder characterized by clonal proliferation of CD3 þ LGL, which is often associated with autoimmune disorders. Phenotypic and functional data suggest that leukaemic CD3þ LGL represent activated cytotoxic T lymphocytes (CTL). One mechanism whereby CTL mediate target cell killing is through the Fas/ Fas ligand apoptotic pathway. Fas ligand is expressed by CTL only after activation. In this study we examined seven pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…The detection of increased IFN-γ expression in most of the patients with or without CTL expansions may imply that CTL-mediated pathophysiology is operative in most of the studied patients and perhaps constitutes a better marker of T-cell-mediated inhibition of hematopoiesis. In general, our results are in agreement with previous reports dealing with increased Fas-L and IFN-γ production in both CIN and LGL patients [26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…The detection of increased IFN-γ expression in most of the patients with or without CTL expansions may imply that CTL-mediated pathophysiology is operative in most of the studied patients and perhaps constitutes a better marker of T-cell-mediated inhibition of hematopoiesis. In general, our results are in agreement with previous reports dealing with increased Fas-L and IFN-γ production in both CIN and LGL patients [26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…35 FasL expression is also increased in malignant lymphomas, Hodgkin's disease and large granular lymphocyte leukemia. 46,47 Whether the increased expression of FasL contributes to the survival and growth of leukemic or dysplastic clones is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Various soluble effectors including Fas-ligand have also been implicated in the pathophysiology of the cytopenias in T-LGL. [20][21][22] The clonal CTL in T-LGL generally resemble an antigen-activated CD8 + CD57 + effector cell, as both constitutively express perforin and Fas-ligand and can suppress neutrophils in vitro. 21,23,24 Gene expression studies have shown that the T-LGL clone exhibits upregulation of cytotoxic proteases and adhesion molecules and downregulation of protease inhibitors.…”
Section: Introductionmentioning
confidence: 99%